A major orbito-hyetal event at the middle-to-late Oxfordian transition (Late Jurassic). (February 2023) - Brikiatis, Leonidas
Abstract: Arido-eustasy is a model that explains palaeoenvironmental change by linking the covariation of the carbon isotope record and the eustatic sea level to orbitally modulated hydroclimatic intensity. Orbitally forced wet climate modes periodically accelerate the water cycle in the biosphere, modulating the balance between terrestrial fresh-water reservoirs and the eustatic sea level and perturbating the carbon cycle through catastrophic weathering of terrestrial carbon reservoirs, resulting in excessive transfer of carbon into the oceans. These intervals of extreme hydroclimatic intensity and weathering, or Orbito-Hyetal Events (OHEs), are hypothesised to be responsible for major palaeoenvironmental crises such as oceanic anoxic events and biotic extinction events. Here, I consider the available data and show evidence for the occurrence of a strong and short-term OHE at the end of the middle Oxfordian. The event probably lasted ∼40 kyr and was bracketed by characteristic arido-eustatic traits, including a prominent sea level fall (the OX5), a contemporaneous extreme (>2‰) negative excursion in the marine carbonate and terrestrial organic-carbon isotope records, and regional occurrences of anoxic environments with organic-rich deposits. Important prolific source-rock reservoirs, such as the Smackover, Hanifa, and Khodjaipak Formations in the Gulf of Mexico, Arabian Gulf, and Uzbekistan, respectively, seem to have been created during this end-middle Oxfordian OHE. Highlights: Reconsidering the extracted information from carbon isotope record. Explaining Mesozoic environmental crises under the terms of an orbitally modulated hydroclimatic intensity. Relating environmental crises with the formation of source rocks. Documenting an environmental crisis in the Middle-to-Late Oxfordian transition.